Cannabidiol versus placebo as adjunctive treatment in early psychosis: study protocol for randomized controlled trial - T. Dixon; K. S. Cadenhead (Trials, 2023)
Abstract Background Psychotic disorders are a leading cause of disability in young adults. Antipsychotics have been the primary intervention for psychosis for over 60 years, and yet, we have made little progress in treating negative symptoms, neurocognition, and functional disability. There is growing evidence that cannabidiol (CBD) is effective in treating positive psychotic symptoms, possibly also negative and neurocognitive symptoms, and moreover is well tolerated compared to other psychotropic medications. Anecdotally, patients participating in the Cognitive Assessment and Risk Evaluation (CARE) Early Psychosis Treatment Program at the University of California, San Diego, are self-administering CBD and report subjective improvement in stress, anxiety, and ability to cope with symptoms. The overarching aim of the trial is to explore the effectiveness of CBD augmentation on symptoms and neurocognition in early psychosis while also exploring the mechanism of action of CBD and predictors of response to treatment. The mechanism by which cannabidiol has a therapeutic effect on psychosis is poorly understood. Recent evidence has suggested that CBD may reduce stress and pro-inflammatory biomarker levels. Endocannabinoids also have powerful roles in eating behavior, reward, and mood, indicating these neurotransmitters may play a role in reducing hyperphagia and metabolic abnormalities that are present early in the course of psychotic illness and exacerbated by antipsychotic medication. The neurophysiological effects of CBD have been studied in animal models of psychosis that show improvements in information processing in response to CBD, but there are no studies in individuals with early psychosis. Method A total of 120 individuals in the early stages of psychosis will be randomized to 1000 mg of CBD versus placebo as an adjunct to existing treatment in a 8-week, double-blind superiority randomized control trial. The primary outcome measures are symptoms and neurocognition. Discussion We hypothesized that CBD will improve symptoms and neurocognition as well as secondary outcome measures of neurohormones, inflammation, eating behaviors, and information processing. Importantly, predictors, moderators, and mediators of the CBD effects will be examined. A better understanding of which individuals are likely to respond to CBD can inform treatment planning and personalize treatment. Trial registration ClinicalTrials.gov NCT04411225. Registered on June 2, 2020.